Silicon Nanowires - Uda, Hashim, Prof. Dr.; Mohammad Nuzaihan, Md Nor; Nur Hamidah, Abdul Halim (Malaysian Invention and Design Society (MINDS), 2010)
Prof. Uda Hashim and his team won gold for Silicon Nanowires. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.